2023
DOI: 10.1021/acs.cgd.3c00317
|View full text |Cite
|
Sign up to set email alerts
|

Nanostars in Highly Si-Doped GaN

Abstract: Understanding the relation between surface morphology during epitaxy of GaN:Si and its electrical properties is important from both the fundamental and application perspectives. This work evidences the formation of nanostars in highly doped GaN:Si layers with doping level ranging from 5 × 1019 to 1 × 1020 cm–3 grown by plasma-assisted molecular beam epitaxy (PAMBE). Nanostars are 50-nm-wide platelets arranged in six-fold symmetry around the [0001] axis and have different electrical properties from the surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Adoption of such growth conditions generally leads to the formation of fragmented islands on the surface of the crystal. In Figure , we show the results obtained after 10 5 time steps, what at room temperature and assuming typical attempt frequency values 10 13 and typical diffusion barrier 0.5 eV translates into time of 2 or 3 s. The shape of obtained islands are dendrite-like and in some sense resembles the experimentally observed structures in highly Si-doped GaN layers . We observed that for higher values of diffusional rate islands grow larger with a more regular and dense structure.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Adoption of such growth conditions generally leads to the formation of fragmented islands on the surface of the crystal. In Figure , we show the results obtained after 10 5 time steps, what at room temperature and assuming typical attempt frequency values 10 13 and typical diffusion barrier 0.5 eV translates into time of 2 or 3 s. The shape of obtained islands are dendrite-like and in some sense resembles the experimentally observed structures in highly Si-doped GaN layers . We observed that for higher values of diffusional rate islands grow larger with a more regular and dense structure.…”
Section: Resultssupporting
confidence: 54%
“…In Figure 2, we show the results obtained after 10 5 time steps, what at room temperature and assuming typical attempt frequency values 10 13 and typical diffusion barrier 0.5 eV translates into time of 2 or 3 s. The shape of obtained islands are dendrite-like and in some sense resembles the experimentally observed structures in highly Si-doped GaN layers. 27 We observed that for higher values of diffusional rate islands grow larger with a more regular and dense structure. To be sure that the structure with lower n DS is not an early stage of structure with higher one, we performed calculations for longer time steps.…”
Section: ■ Results and Discussionmentioning
confidence: 57%